Epidemiological Study on Infectious Bursal Disease in Broilers - Macwan, Terrance S.; Dave, C.J.; Joshi , B.P.; Ghodasara , D.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was carried out to know the epidemiology of Infectious bursal disease (IBD) in and around Anand district of Gujarat state. The study comprised of autopsy incidences of mortality from the retrospective data of the Department of Veterinary Pathology, Anand and farm wise mortality data from 25 affected farms with IBD selected for detailed study, irrespective of their vaccination status. The retrospective year wise autopsy incidence of last five years (January 2013 to December 2017) ranged between 1.42 and 8.38% with an overall average of 4.93%. The highest incidence was seen during the months of monsoon season (July-October; 57%, absolute mortality 8.28- 10.72%) followed by summer (27%) and winter (16%), and also in the age groups of 3rd and 4th week of age (39.46 and 37.57%). The flock wise mortality among 25 affected broiler flocks varied from 0.29 to 9.44 % with an average of 1.36% (1953/143400). It was also more in non-vaccinated than vaccinated population (1.76 vs. 0.94%). Findings of the present work confirmed an increasing trend of IBD infections in the commercial broiler farms despite of vaccination.
Keywords: Broiler; Infectious bursal disease; Epidemiology; Bursa of Fabricius